Influence of Cupressus lusitanica Mill. Cones and Seed Characterization on Germination in Kenya - Angaine, Peter Murithi; Onyango, Alice Adongo; Ndung’u, Stephen Muriithi; Inoti, Shadrack Kinyua; Owino, Jesse O (Journal of Forests, 2021)
Cupressus lusitanica is a key plantation species with many uses leading to demand for seed. This species produces seeds within cones, which are collected for seed extraction. There are variations in seed collection and handling which compromise quality. Few studies focus on cone morphometry and seed characterization, thereby causing a gap in quality improvement through packaging and subsequent germination. Fifty cones were collected from each of the thirty identified trees within a clonal seed orchard. Cone characterization, seed extraction and germination were performed in the laboratory. This was a factorial experiment with three factors: cone diameter, seed diameter and seed density and their influences on germination. The present study separated the cones by diameter (20mm sieve) and weight. Seed were sieved (2mm sieve) weighed, floated and germinated. The results showed that seed size and density heavily impacted on germination and thereby showing that sorting through sieving and floatation would provide a low cost technique for seed quality improvement. The technique in the present study improved germination from 25% to 50%, and also reduced the number of seeds per kilogram from 290,000 to 105,000.